Postmodern Yaklaşımın Tarih Eğitimine Yansımaları - Koruroğlu, Ayten (Journal of History Culture and Art Research, 2019)
Reflections of Postmodern Approach to History Education Abstract Postmodernism is characterized as a concept following the modernity and it is referred together with the concepts of deconstructionism or post-structuralism. Postmodernism, which is used in the meaning of the future of modernism, has an attitude against modernism. Today, the debate on postmodernism and modernism has not ended yet. Postmodernists see the world as a pattern which is alterable and diverse. The concept of postmodern history is against the traditional concept of history. As the postmodernism gives importance to popular culture, it argues that it is necessary to use local and oral history methods in the writing of history. Persons and groups who have not entered the history textbooks should be studied, the events that are important to the local community should be examined and discussed, and daily life should be addressed. Postmodernism places importance on localism and local culture. In this context, postmodernism considers verbal history as the most appropriate approach to the study of local history. The purpose of this research is to explain the reflections of postmodern education in history education. The research is a study in documentary screening type. For the collection of research data, research related to the subject were used. In this research, the concept of postmodernism is tried to be explained and the effects of this concept on education, especially history education, are discussed. As a result of the nature of postmodernism, it has brought a new perspective to traditional history and history education. Although this perspective has been widely accepted by traditionalist historians, it has been adopted by many innovative historians, because of the new approaches in education. Especially constructivism, the reflection of the postmodernist approach, is a widely accepted conception today. In this context, understanding postmodernism as a concept and studying its reflections on history education are the main purpose in this research. The concept of postmodern history is seen as an understanding of local and verbal history. Therefore, in this research, the concepts of local and verbal history have been tried to be explained by also using the literature review. Postmodern Yaklaşımın Tarih Eğitimine Yansımaları Öz Postmodernizm, modern sonrası olarak nitelendirilmekte, yapıbozumculuk veya post-yapısalcılık kavramlarıyla birlikte anılmaktadır. Modernin ilerisinde anlamında kullanılan postmodernizim, modernizme karşı bir tavır sergilemektedir. Bugün halen postmodernizm ve modernizm tartışmaları son bulmuş değildir. Postmodernistler dünyayı değişebilir ve çeşitli bir desen olarak görmektedirler. Postmodern tarih anlayışı ise, geleneksel tarih anlayışına karşıdır. Postmodernizm popüler kültüre önem verdiği için, tarih yazımında yerel ve sözlü tarih yöntemlerinden yararlanılması gerektiğini savunmaktadır. Tarih ders kitaplarına girmemiş kişi ve gruplar araştırılmalı, yerel toplumca önemli görülen olaylar incelenip ele alınmalı, gündelik hayat işlenmelidir. Postmodernizm yerelliğe ve yerel kültüre önem vermektedir. Bu bağlamda postmodernizm yerel tarihin incelenmesine en uygun yaklaşım olarak sözlü tarihi görmektedir. Araştırmanın amacı postmodern eğitim anlayışının tarih eğitimindeki yansımaları açıklamaktır. Araştırma, belgesel tarama türünde bir çalışmadır. Araştırma verilerinin toplanması için konu ile ilgili araştırmalar harmanlanarak kullanılmıştır. Yapılan araştırmada öncelikle postmodernizim kavramı açıklanmaya çalışılmış olup bu kavramın eğitime özellikle tarih eğitimine etkileri tartışılmıştır. Postmodernizmin doğası gereği her alana yenilik getirmiş olduğu gibi geleneksel tarih anlayışına ve tarih eğitimine de farklı bir bakış açısı getirmiştir. Bu bakış açısı gelenekselci tarihçiler tarafından pek kabul görmese de günümüzde eğitimdeki yeni yaklaşımlar dolayısı ile pek çok yenilikçi tarihçi tarafından da benimsenmiştir. Özellikle postmodern yaklaşımın yansıması yapılandırmacılık günümüzde çok kabul gören bir anlayış durumundadır. Bu bağlamda bu çalışmada kavram olarak postmodernizimi anlamak ve özellikle tarih eğitmine yansımalarını incelemek ana hedef olmuştur. Postmodern tarih anlayışı ise karşımıza yerel ve sözlü tarih anlayışı olarak karşımıza çıkmaktadır. Bu nedenle yapılan araştırmada yerel ve sözlü tarih kavramları da kaynak taraması yapılarak açıklanmaya çalışılmıştır.